NURSING STUDENT’S PERCEPTIONS OF THEIR EDUCATIONAL ENVIRONMENT IN AN ARMED FORCES NURSING COLLEGE - A CROSS SECTIONAL STUDY - Shaheen, Dr. Nirgis; Hamdani, Dr. Usman; Roshan, Dr. Rukhsana; Shaheen, Dr. Farid Asif; Azam, Dr. Naila; Pervaiz, Dr. Farrah; Mahmood, Dr. Humaira (Pakistan Armed Forces Medical Journal, 2019)
Objective: To evaluate the progress and refining the educational environment for nursing students in Pakistan Armed Forces. Study Design: Descriptive cross-sectional study. Place and Duration of Study: College of nursing AFPGMI Rawalpindi from Mar to Aug 2018. Material and Methods: The study population consists of 303 nursing students from college of nursing Rawalpindi. Structured validated data collection tool e.g. DREEM questionnaire has been used to evaluate the educational environment. Results: The total mean score of DREEM at College of nursing AFPGMI was 132.6/200 (66.3%). The total score of Students perceptions of learning domain was 32.8/48 (68.33%). Student’sperceptions of teaching domain were 27.5/44 (62.5%), while that of SASP was 22.5/32 (70.3%). Student’s perception of atmosphere domain was 32.4/48 (67.5%) and that of SSP was 17.4/28 (62.1%). For SPL, SPT, SASP, and SPA domains the score was ≥50%. However for SASP domain achieves the highest score was 70.3%. Conclusion: Total DREEM score at CON AFPGMI RWP was more positive than negative. There is need to enhancement and upgrading because consequence attained between 2 to 3.16. It also highlights issues like support system for students who get hassled.